THE ATTEMPT TO RECONQUEST SPANISH AND THE CONSTRUCTION OF THE HEROIC IMAGE OF ANTONIO LÓPEZ DE SANTA ANNA. THE CASE OF THE MILITARY ACTION OIL PAINTING IN PUEBLO VIEJO, 1829 (Tzintzun, Revista de Estudios Históricos, 2024)
The article analyzes historically and aesthetically the oil painting Military Actionin Pueblo Viejo, 1829, by Carlos Paris, which represents the victory of the Mexicanarmy over the Hispanic expedition, in its intention to reconquer the old NewSpain, to determine it as a starting point for the construction of the heroic imageof General Antonio López de Santa Anna, which -together with the epic narrativethat permeated those years-, allowed him to constitute the preponderant political/military figure of the first half of the Mexican nineteenth century: the humanrepresentation of the young nation.
Keywords: Mexico; Spain; painting; hero; Santa-Anna